Test of Mercury (Hg) Content in Mozambique Tilapia Fish (Oreochromis Mossambicus) from Lake Rawa Taliwang Nature Tourism Park, West Sumbawa Regency - Hadiatullah; Khairuddin; Didik Santoso (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Rawa Taliwang Lake Natural Tourism Park is a freshwater waters located in West Sumbawa Regency with an area of ​​819.20 ha. Rawa Taliwang Lake Natural Tourism Park is dominated by various types of fish, so that local people catch fish in this lake to meet their consumption needs and for sale. In addition, the lake's catchment area also holds mining potential, especially gold. Small-scale gold mining, mostly found in the mountains and hills around catchment area Lake Rawa Taliwang. This mining uses liquid mercury as a gold binder from the ore. Some waste that has an impact on the end of lake water so that it can affect the lake ecosystem. Therefore, research is needed to determine the amount of mercury (Hg) in tilapia mozambique fish (Oreochromis mossambicus) from Rawa Taliwang Lake Natural Tourism Park. This study uses a quantitative descriptive method. In this study, sampling was carried out by purposive sampling at 3 location points with 3 repetitions. The research sample used 9 tilapia Mozambique fish. The data obtained were analyzed using the Atomic Absorption Spectrophotometry (AAS) method. The results showed that the mercury content in tilapia mozambique fish was < 0.001 ppm. So it can be said that in the flesh of tilapia fish no heavy metal mercury (Hg) was detected.